MEDICATION ERROR OF EXPIRED DRUGS FOR AMBULATORY PATIENTS - Vitrianingsih, Yeni; Suhartono, Slamet; Mangesti, Yovita Arie; Budiarsih (jfpublisher, 2023)
Medication errors are commonly found in patient prescriptions. In Article 12 of the Pharmaceutical Law, these cases are only subject to administrative sanctions. It is also stated in the Minister of Health Regulation No. 72/2016 Articles 3 and 12 that the sanctions imposed are only administrative sanctions in accordance with the provisions of laws and regulations. The regulation is quite unclear, and will be clarified in the discussion of this research to identify laws that provide protection for ambulatory patients. The high problem of medication errors in patients indicates that it is required to take real action to prevent these cases to occur which cause detriment to the patient. Therefore, the objective of this research is to determine the factors that cause medication errors in the prescribing and dispensing phases. The research method used in this research is normative research with prospective data collection techniques which both methods can provide an overview and accuracy of data regarding the problem of medication errors on expired medicines. The results indicated that the factors causing medication errors in the prescribing phase and dispensing phase, such as work distractions such as ringing telephones, workload on health workers who are unable to do each job themselves, miscommunication between doctors and pharmacists about the use of drugs for patients, unsupported conditions while working, and education on writing prescriptions that do not comply with the requirements for completeness of prescriptions; the lack of a drug preparation room; and education regarding drug preparation that is not in accordance with prescription requests.